Manajemen Fase Akut Caustic Acidic Injury di Fasilitas tanpa Endoskopi – Laporan Kasus - Stephanie Elaine (Yayasan Pendidikan Medika Indonesia, 2024)
Introduction : Ingesting corrosive substances is a common problem in developing countries because of the easy access to these substances, most of which are alkaline. More than 200,000 cases have been reported in the United States, 10% of the population being adults. In Thailand, 19.5% of cases of ingestion of corrosive materials were found. Acidic and alkaline substances will provide different types of tissue damage. Acidic substances will cause coagulation necrosis with the formation of eschar which can limit further penetration, while bases cause saponification. Appropriate management in the acute phase can prevent further damage and facilitate management in the chronic phase. The following is a case report regarding the acute management of an adult woman who swallowed a corrosive substance. Case Illustration : A 41 year old woman was referred from the Regional Hospital on the 5th day of treatment with complaints of pain in swallowing accompanied by heartburn after drinking Porstex liquid. When the patient came to the RSUD emergency room in a condition of decreased consciousness and vomiting blood. On initial examination, she was delirium with GCS E3M5V3 with BP hypotension, with normal RR and Oxygen Saturation. The initial supporting examination is a complete blood count (Hb: 15.9, leukocytes: 24,630, platelets: 379.000), normal kidney and liver function, electrolytes within normal limits and no signs of gastric perforation were found in the abdominal X-ray examination. The patient was stabilized by loading crystalloid fluids, installing an NGT, administering PPI injection therapy, antibiotics, anti-bleeding, sucralfate and the patient was completely fasted. On the 5th day of treatment, it was found that the patient had improved hemodynamics and was referred to K Hospital with endoscopy facilities because the NGT production was still black. While at K Hospital the patient underwent another laboratory examination with the results showing hypokalemia (K = 2.9, with GDS = 61). The patient then undergoes electrolyte correction, hypoglycemia protocol, the previous medication is continued and the patient remains fasted. On the 7th day, the patient underwent laryngoscopy with a modified bronchoscopy scope, with the result of laryngitis oropharyngitis. The patient then went home with the NGT still installed. The patient was controlled on the 18th day after the incident with complaints of heartburn that had improved, there was no pain in swallowing, the patient was on a liquid diet, and the NGT was clear so the NGT was then removed and no further endoscopic examination was carried out. Conclusion : A 41 year old female patient with a history of swallowing corrosive objects presented with acute complications in the form of hypovolemic shock accompanied by hematemesis. The patient underwent resuscitation and conservative treatment and did not undergo endoscopy due to hemodynamic instability. NGT placement is carried out carefully to maintain esophageal patency and observe gastric production. Appropriate acute management can be influential in preventing further damage especially in settings with limited resources. In addition, consideration should be given to referring to a place with endoscopy facilities during the acute phase (<96 hours) to determine diagnostics and prognostics.